Blasting hole-sealing waterproof material with low reaction temperature and rapid solidification function

By using component A composed of components such as magnesium oxide and component B composed of components such as potassium dihydrogen phosphate, rapid solidification and high-strength sealing are achieved at low reaction temperatures, and the long solidification time and pressure resistance of existing materials are solved. The problem of insufficient anti-seepage performance improves the application effect of sealing materials.

CN119409468APending Publication Date: 2025-02-11BASF HOCK MINING CHEM CHINA
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411378713.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing pore sealing materials have a long solidification time at low reaction temperatures, making it difficult to quickly form an effective pore sealing structure, and the compressive and impermeability resistance are insufficient, which poses safety hazards and discontinuity in construction.

Method used

Component A consisting of magnesium oxide, metakaolin, calcium fluorotitanate, lithium carbonate, nanozirconia and water, as well as potassium dihydrogen phosphate, borax, lithium phosphate, ultrafine calcium carbonate and polytetrafluoroethylene particles Component B, through the interaction between components, achieves rapid solidification and high-strength sealing.

Benefits of technology

It achieves rapid solidification at low reaction temperatures, significantly improving the compressive strength and permeability of the material, ensuring the stability of the sealing structure, safety and continuity of construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005069342180000061
    Figure BDA0005069342180000061
  • Figure BDA0005069342180000071
    Figure BDA0005069342180000071
  • Figure BDA0005069342180000081
    Figure BDA0005069342180000081
Patent Text Reader

Abstract

The invention provides a blasting hole sealing waterproof material with a low reaction temperature and a rapid solidification function, and belongs to the technical field of hole sealing materials. The blasting hole sealing waterproof material comprises a component A and a component B, the component A is prepared from magnesium oxide, metakaolin, calcium fluotitanate, lithium carbonate, nano zirconium oxide and water; the component B is prepared from monopotassium phosphate, borax, lithium phosphate, superfine calcium carbonate and polytetrafluoroethylene particles. The two components are mixed according to the volume ratio of 1: 1. The material can be rapidly solidified at a low reaction temperature, the compression resistance and the impermeability are remarkably improved, the material is suitable for occasions such as underground engineering, tunneling and coal mine excavation, and the problem that the performance of an existing hole sealing material is reduced under moisture permeation is solved. In addition, the adopted preparation method is simple and easy to implement, and the excellence and the application effect of the material are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sealing materials, and in particular relates to a blasting sealing waterproof material with low reaction temperature and rapid solidification functions. Background Art

[0002] In underground engineering, tunneling, mining and other blasting construction, the performance of sealing materials directly affects the blasting effect and engineering safety. Sealing materials not only need to solidify quickly, fill pores and form a stable structure, but also have excellent waterproof, anti-seepage and pressure resistance. Especially in underground environments with high water content, the material's anti-seepage performance is particularly critical. If the sealing material cannot effectively prevent the infiltration of groundwater, the water will gradually erode the material, resulting in a decrease in material performance, an increase in pores, and even leakage, which seriously threatens the safety and durability of the construction.

[0003] However, traditional sealing materials in the prior art often find it difficult to balance rapid solidification, compressive strength and impermeability. Most sealing materials may exhibit good solidification performance in the early stages of construction, but when exposed to moisture for a long time, their impermeability is insufficient, and they are prone to leakage and strength decay. Especially under the special conditions of blasting construction, the challenges faced by sealing materials are even more severe. In addition to dealing with the problem of high-pressure groundwater infiltration, the materials must also solidify quickly under a low reaction temperature environment to ensure the continuity of construction. However, the hydration reaction rate of traditional materials at low reaction temperatures is slow, and the solidification time is too long, making it difficult to quickly form an effective sealing structure. If the material cannot solidify in time at a low reaction temperature, moisture will have more time to penetrate into the material, causing irreversible damage. In addition, the reaction temperature of existing materials is also high, which can easily trigger premature reactions of explosive packs or detonators before blasting, posing a safety hazard.

[0004] Therefore, there is an urgent need to develop a low-reaction-temperature rapid blasting sealing waterproof material that can solidify rapidly in a low-reaction-temperature environment and possess good compression and impermeability properties, thereby improving the stability and safety of the sealing material in complex underground environments. Summary of the invention

[0005] The object of the present invention is to provide a blasting sealing waterproof material with low reaction temperature and rapid solidification function, so as to improve the application effect of the sealing material.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] First, the present invention provides a blasting hole sealing waterproof material with low reaction temperature and rapid solidification function, wherein the blasting hole sealing waterproof material is composed of component A and component B;

[0008] The component A is composed of magnesium oxide, metakaolin, calcium fluorotitanate, lithium carbonate, nano zirconium oxide and water;

[0009] The component B consists of potassium dihydrogen phosphate, borax, lithium phosphate, ultrafine calcium carbonate and polytetrafluoroethylene particles.

[0010] Preferably, the volume ratio of component A to component B in the blasting sealing waterproof material is 1:1.

[0011] Preferably, in terms of weight percentage, the component A consists of 40 to 62 parts of magnesium oxide, 20 to 27 parts of metakaolin, 10 to 20 parts of calcium fluorotitanate, 5 to 10 parts of lithium carbonate, 2 to 5 parts of nanomaterials and 70 parts of water.

[0012] Preferably, in terms of weight percentage, the component B consists of 60-75 parts of potassium dihydrogen phosphate, 10-25 parts of borax, 5-8 parts of lithium phosphate, 5-10 parts of ultrafine calcium carbonate, 2-3 parts of polytetrafluoroethylene particles and 100 parts of water.

[0013] Preferably, in terms of mass fractions, the component A is composed of 53 parts of magnesium oxide, 25 parts of metakaolin, 15 parts of calcium fluorotitanate, 5 parts of lithium carbonate, and 2 parts of nano zirconium oxide;

[0014] The component B is composed of 69 parts of potassium dihydrogen phosphate, 15 parts of borax, 6 parts of lithium phosphate, 8 parts of ultrafine calcium carbonate, and 2 parts of polytetrafluoroethylene particles.

[0015] Preferably, the particle size of the magnesium oxide is 200 mesh, the particle size of the metakaolin is 200 mesh, the particle size of the calcium fluorotitanate is 200 mesh, the particle size of the lithium carbonate is 1200 mesh, the particle size of the nano zirconium oxide is 30 nm, the particle size of the borax is 60 mesh, the particle size of the ultrafine calcium carbonate is 800 mesh, and the particle size of the polytetrafluoroethylene particles is 5 μm.

[0016] Preferably, the blasting sealing waterproof material is prepared by the following preparation method:

[0017] (1) mixing magnesium oxide, metakaolin, calcium fluorotitanate, lithium carbonate, nano zirconium oxide and water and stirring them uniformly to obtain component A;

[0018] (2) mixing potassium dihydrogen phosphate, borax, lithium phosphate, ultrafine calcium carbonate, polytetrafluoroethylene particles and water and stirring them uniformly to obtain component B;

[0019] (3) Component A and component B are mixed in a volume ratio of 1:1 to obtain a blasting sealing waterproof material.

[0020] Secondly, the present invention provides a method for preparing a blasting sealing waterproof material with low reaction temperature and rapid solidification function, characterized in that the preparation method comprises the following steps:

[0021] (1) 40 to 62 parts of magnesium oxide, 20 to 27 parts of metakaolin, 10 to 20 parts of calcium fluorotitanate, 5 to 10 parts of lithium carbonate, 2 to 5 parts of nano zirconium oxide and water are mixed and stirred to obtain component A;

[0022] (2) 60 to 75 parts of potassium dihydrogen phosphate, 10 to 25 parts of borax, 5 to 8 parts of lithium phosphate, 5 to 10 parts of ultrafine calcium carbonate, 2 to 3 parts of polytetrafluoroethylene particles and 100 parts of water are mixed and stirred to obtain component B;

[0023] (3) Component A and component B are mixed in a volume ratio of 1:1 to obtain a blasting sealing waterproof material.

[0024] Preferably, the particle size of the magnesium oxide is 200 mesh, the particle size of the metakaolin is 200 mesh, the particle size of the calcium fluorotitanate is 200 mesh, the particle size of the lithium carbonate is 1200 mesh, the particle size of the nano zirconium oxide is 30 nm, the particle size of the borax is 60 mesh, the particle size of the ultrafine calcium carbonate is 800 mesh, and the particle size of the polytetrafluoroethylene particles is 5 μm.

[0025] The beneficial effects of the present invention are:

[0026] The sealing material of the present invention achieves a rapid solidification effect, and through the interaction between the components, extremely short initial and final setting times are achieved, showing excellent rapid solidification ability. Magnesium oxide, as a core rapid hardening material, accelerates the hydration process through chemical reactions with other components (such as calcium fluorotitanate, lithium phosphate, lithium carbonate, etc.). This synergistic effect ensures that the material can achieve rapid sealing in an emergency construction environment.

[0027] The sealing material of the present invention achieves an improvement in compressive strength. Through the combined action of different components, a dense microstructure is formed inside the material, which significantly improves the compressive strength of the material. The combination of magnesium oxide, metakaolin and other components produces a highly dense crystal structure that fills the pores in the material. Nano- and ultra-fine-grade materials (such as nano-zirconia and ultra-fine calcium carbonate) further optimize the microscopic distribution of the material, making the reaction more uniform and the structure more compact.

[0028] The sealing material of the present invention achieves a significant improvement in the anti-seepage performance, and the anti-seepage performance of the material is also enhanced by the interaction between the components. During the hydration reaction, the components form a highly dense structure, which seals the pores and microcracks in the material and prevents the penetration of water. The introduction of nano zirconium oxide and polytetrafluoroethylene particles further improves the waterproof ability of the material, and the anti-seepage effect of the material is significantly enhanced by filling the tiny pores. This synergistic effect ensures that the material can maintain good waterproof performance for a long time in an underground environment with a high water content, and the problem of water penetration causing material failure will not occur. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] A fast blasting sealing waterproof material with low reaction temperature

[0032] 53 parts of magnesium oxide (200 mesh), 25 parts of metakaolin (200 mesh), 15 parts of calcium fluorotitanate (200 mesh), 5 parts of lithium carbonate (1200 mesh), 2 parts of nano zirconium oxide with a particle size of 30 nm and 70 parts of water were put into a stirrer and stirred for 20 minutes. After mixing evenly, component A was obtained;

[0033] 69 parts of potassium dihydrogen phosphate, 15 parts of borax (60 mesh), 6 parts of lithium phosphate (1200 mesh), 8 parts of ultrafine calcium carbonate (800 mesh), 2 parts of polytetrafluoroethylene particles (5 μm) and 100 parts of water were put into a stirrer and stirred for 20 minutes. After mixing evenly, component B was obtained;

[0034] Mix component A and component B in a ratio of 1:1 to obtain a fast blasting sealing waterproof material with a low reaction temperature.

[0035] Example 2

[0036] The preparation method is the same as that of Example 1, except that: magnesium oxide is 40 parts, metakaolin is 27 parts, calcium fluorotitanate is 10 parts, lithium carbonate is 10 parts, nano zirconium oxide is 5 parts, potassium dihydrogen phosphate is 60 parts, borax is 10 parts, lithium phosphate is 8 parts, ultrafine calcium carbonate is 5 parts, and polytetrafluoroethylene particles are 3 parts.

[0037] Example 3

[0038] The preparation method is the same as that of Example 1, except that: magnesium oxide is 62 parts, metakaolin is 20 parts, calcium fluorotitanate is 20 parts, lithium carbonate is 5 parts, nano zirconium oxide is 3 parts, potassium dihydrogen phosphate is 75 parts, borax is 25 parts, lithium phosphate is 5 parts, ultrafine calcium carbonate is 10 parts, and polytetrafluoroethylene particles are 4 parts.

[0039] Comparative Example 1

[0040] The preparation method is the same as that of Example 1, except that the metakaolin is replaced with mineral powder.

[0041] Comparative Example 2

[0042] The preparation method is the same as that of Example 1, except that no calcium fluorotitanate is added.

[0043] Comparative Example 3

[0044] The preparation method is the same as that of Example 1, except that no lithium carbonate is added.

[0045] Comparative Example 4

[0046] The preparation method is the same as that of Example 1, except that nano zirconium oxide is replaced by nano calcium oxide.

[0047] Comparative Example 5

[0048] The preparation method is the same as that of Example 1, except that lithium phosphate is replaced by aluminum hydroxide.

[0049] Comparative Example 6

[0050] The preparation method is the same as that of Example 1, except that no ultrafine calcium carbonate is added.

[0051] Comparative Example 7

[0052] The preparation method is the same as that of Example 1, except that no polytetrafluoroethylene particles are added.

[0053] Comparative Example 8

[0054] The preparation method is the same as that of Example 1, except that the ultrafine calcium carbonate is 600 mesh ultrafine calcium carbonate.

[0055] Comparative Example 9

[0056] The preparation method is the same as that of Example 1, except that the nano zirconium oxide has a particle size of 50 nm.

[0057] Comparative Example 10

[0058] The preparation method is the same as that of Example 1, except that the polytetrafluoroethylene particles are nano-zirconia particles with a particle size of 20 μm.

[0059] Comparative Example 11

[0060] The commercially available blasting sealing materials were purchased from Jinding Company.

[0061] The sources of some materials used in the present invention are as follows: magnesium oxide and metakaolin were purchased from BASF, calcium fluorotitanate was purchased from Jinjinle Chemical Co., Ltd., lithium carbonate was purchased from Shandong Hezhan Chemical Co., Ltd., lithium phosphate was purchased from Shandong Xingfu New Materials Co., Ltd., and polytetrafluoroethylene particles were purchased from Shanghai Jieshikai Biotechnology Co., Ltd.

[0062] Experimental test 1

[0063] First, the present invention detects the difference between the average initial setting time and the average final setting time of the sealing materials prepared in the embodiment and the comparative example. The obtained results are shown in Table 1.

[0064] Table 1 Differences in solidification time of different sealing materials

[0065]

[0066]

[0067] From the results in Table 1, it can be seen that Example 1 exhibits the fastest initial setting and final setting times, proving that it has the best rapid solidification performance. The synergistic effect of each component is significant, and it is suitable for projects requiring rapid solidification and high-strength sealing.

[0068] Examples 2 and 3 also exhibit good solidification performance. Although they are slightly slower than Example 1, they still maintain rapid solidification, proving that the optimized ratio of different components significantly improves the material properties.

[0069] From Comparative Example 1 (missing kaolin), Comparative Example 2 (missing calcium fluorotitanate), Comparative Example 3 (missing lithium carbonate) and Comparative Example 6 (missing ultrafine calcium carbonate), the initial and final setting times of these formulations are significantly extended, indicating that the lack of key components has led to a significant decrease in material performance.

[0070] In Comparative Example 4 (nano-zirconium oxide is replaced by nano-calcium oxide) and Comparative Example 5 (lithium phosphate is replaced by aluminum hydroxide), the initial and final setting times are prolonged after replacement, indicating that after replacing some components in Example 1, the effect achieved in Example 1 cannot be achieved, but the overall effect is better than the effect of missing some components.

[0071] Comparative Example 8 (600 mesh ultrafine calcium carbonate), Comparative Example 9 (50nm particle size nano zirconium oxide) and Comparative Example 10 (20μm particle size polytetrafluoroethylene particles), although these changes lead to extended solidification time, the impact is smaller than the lack or replacement of components. This shows that the use of ultrafine calcium carbonate with different meshes and nano zirconium oxide and polytetrafluoroethylene particles with different particle sizes will also affect the solidification effect of the final material. Although the difference is smaller than the lack and replacement of components, there is still a huge difference from Example 1.

[0072] The initial setting and final setting times of the commercially available material (Comparative Example 11) are the slowest, and it cannot meet the effect of rapid solidification.

[0073] The above results show that the synergistic effect of the components in Example 1 effectively shortens the initial setting and final setting times. However, when the components are missing, replaced, or the mesh size / particle size changes, the reaction speed of the material will be affected to varying degrees.

[0074] Experimental test 2

[0075] The present invention tests the 1h average compressive strength, maximum reaction temperature and anti-seepage pressure of the sealing materials prepared in the examples and comparative examples. The results are shown in Table 2.

[0076] Table 2 Differences in average compressive strength, maximum reaction temperature and impermeability pressure of different sealing materials

[0077]

[0078] From the results in Table 2, Example 1 exhibits the highest compressive strength, the lowest reaction temperature and the best impermeability pressure, which indicates that the formula has excellent high strength, low temperature reaction and excellent impermeability, and is very suitable for the engineering requirements of high strength and low temperature blasting sealing method. Although Examples 2 and 3 also exhibit good compressive strength and impermeability, and their low reaction temperatures are still maintained at a relatively high level, their performance is slightly insufficient compared to Example 1.

[0079] From Comparative Example 1 (missing metakaolin), Comparative Example 2 (missing calcium fluorotitanate), Comparative Example 3 (missing lithium carbonate), and Comparative Example 6 (missing ultrafine calcium carbonate), it can be clearly seen that the overall formula of the present invention is indispensable. The lack of any component will have a significant impact on the compressive strength, impermeability and reaction temperature, emphasizing the importance of each component in the formula.

[0080] From Comparative Example 4 (nano zirconium oxide is replaced by nano calcium oxide) and Comparative Example 5 (lithium phosphate is replaced by aluminum hydroxide), it can be seen that when some components in Example 1 are replaced with the same type of substances, the effect achieved by Example 1 cannot be achieved, indicating that there is a synergistic effect between the components of Example 1, and once some of the components are replaced, the effect cannot be achieved.

[0081] From Comparative Example 8 (600 mesh ultrafine calcium carbonate), Comparative Example 9 (50nm particle size nano zirconium oxide), and Comparative Example 10 (20μm particle size polytetrafluoroethylene particles), it can be seen that the particle size of different components will also have a significant impact on the final effect. Therefore, only when the components, proportions, and particle sizes used in Example 1 are used can a significant synergistic effect be produced. Once replaced or missing, the technical effect to be achieved by the present invention cannot be achieved.

Claims

1. A blasting sealing waterproof material with low reaction temperature and rapid solidification function, characterized in that: The blasting sealing waterproof material consists of component A and component B; The component A is composed of magnesium oxide, metakaolin, calcium fluorotitanate, lithium carbonate, nano zirconium oxide and water; The component B consists of potassium dihydrogen phosphate, borax, lithium phosphate, ultrafine calcium carbonate and polytetrafluoroethylene particles.

2. The blasting sealing waterproof material according to claim 1, characterized in that: The volume ratio of component A to component B in the blasting sealing waterproof material is 1:

1.

3. The blasting sealing waterproof material according to claim 2, characterized in that: Calculated by weight, the component A consists of 40 to 62 parts of magnesium oxide, 20 to 27 parts of metakaolin, 10 to 20 parts of calcium fluorotitanate, 5 to 10 parts of lithium carbonate, 2 to 5 parts of nanomaterials and 70 parts of water.

4. The blasting sealing waterproof material according to claim 3, characterized in that: Calculated by weight, the component B consists of 60-75 parts of potassium dihydrogen phosphate, 10-25 parts of borax, 5-8 parts of lithium phosphate, 5-10 parts of ultrafine calcium carbonate, 2-3 parts of polytetrafluoroethylene particles and 100 parts of water.

5. The blasting sealing waterproof material according to claim 4, characterized in that: In terms of weight, the component A is composed of 53 parts of magnesium oxide, 25 parts of metakaolin, 15 parts of calcium fluorotitanate, 5 parts of lithium carbonate, and 2 parts of nano zirconium oxide; The component B is composed of 69 parts of potassium dihydrogen phosphate, 15 parts of borax, 6 parts of lithium phosphate, 8 parts of ultrafine calcium carbonate, and 2 parts of polytetrafluoroethylene particles.

6. The blasting sealing waterproof material according to claim 5, characterized in that: The particle size of the magnesium oxide is 200 mesh, the particle size of the metakaolin is 200 mesh, the particle size of the calcium fluorotitanate is 200 mesh, the particle size of the lithium carbonate is 1200 mesh, the particle size of the nano zirconium oxide is 30 nm, the particle size of the borax is 60 mesh, the particle size of the ultrafine calcium carbonate is 800 mesh, and the particle size of the polytetrafluoroethylene particles is 5 μm.

7. The blasting sealing waterproof material according to claim 6, characterized in that: The blasting sealing waterproof material is prepared by the following preparation method: (1) mixing magnesium oxide, metakaolin, calcium fluorotitanate, lithium carbonate, nano zirconium oxide and water and stirring them uniformly to obtain component A; (2) mixing potassium dihydrogen phosphate, borax, lithium phosphate, ultrafine calcium carbonate, polytetrafluoroethylene particles and water and stirring them uniformly to obtain component B; (3) Component A and component B are mixed in a volume ratio of 1:1 to obtain a blasting sealing waterproof material.

8. A method for preparing a blasting sealing waterproof material with low reaction temperature and rapid solidification function, characterized in that: The preparation method comprises the following steps: (1) 40 to 62 parts of magnesium oxide, 20 to 27 parts of metakaolin, 10 to 20 parts of calcium fluorotitanate, 5 to 10 parts of lithium carbonate, 2 to 5 parts of nano zirconium oxide and water are mixed and stirred to obtain component A; (2) 60 to 75 parts of potassium dihydrogen phosphate, 10 to 25 parts of borax, 5 to 8 parts of lithium phosphate, 5 to 10 parts of ultrafine calcium carbonate, 2 to 3 parts of polytetrafluoroethylene particles and 100 parts of water are mixed and stirred to obtain component B; (3) Component A and component B are mixed in a volume ratio of 1:1 to obtain a blasting sealing waterproof material.

9. The preparation method according to claim 8, characterized in that: The particle size of the magnesium oxide is 200 mesh, the particle size of the metakaolin is 200 mesh, the particle size of the calcium fluorotitanate is 200 mesh, the particle size of the lithium carbonate is 1200 mesh, the particle size of the nano zirconium oxide is 30 nm, the particle size of the borax is 60 mesh, the particle size of the ultrafine calcium carbonate is 800 mesh, and the particle size of the polytetrafluoroethylene particles is 5 μm.

Citation Information

Cited By

  • High-lubrication nickel-free hole sealing agent as well as preparation method and application thereof

    CN121250498A